'A Pest to Society': The Charity Organisation Society's Domiciliary Assessments into the Circumstances of Poor Families and Children. (24th August 2017) - Skinner, Annie; Thomas, Nigel
Abstract : This article examines the work of the Charity Organisation Society (COS) in assessing applications for children's admission to care in the late nineteenth‐century. It is based on an archive study of records kept by the 'Waifs and Strays' Society in England and Wales between 1882 and 1899, in particular 270 family assessments conducted by the COS. The focus was on parental behaviour rather than children's needs, with a strong narrative of taking children away to relieve parents of a burden. The research illuminates contested assumptions about childhood in the period, with resonance for current issues in policy and practice.